Chronic Staphylococcus aureus Superantigen Toxic Shock Syndrome Toxin-1 Exposure Accelerates the Progression of Atherosclerosis in Rabbits - Zhao, Huanqiang (Taiwan Society of Cardiology, 2020)

(untitled) (Acta Cardiol Sin)
BACKGROUND: It has been reported that infectious agents contribute to the atherosclerotic process. However, it is unclear whether Staphylococcus aureus superantigen (SAg) toxic shock syndrome toxin-1 (TSST-1) has an effect on atherosclerosis progression. The present study was designed to investigate the pathogenic role of TSST-1 exposure in the atherosclerotic process in rabbits. METHODS: New Zealand White rabbits were exposed to TSST-1 through Alzet miniosmotic pumps with a constant pumping rate. Aortic atherosclerosis was evaluated by histological and morphometric methods. Using a biochemical analyzer/enzyme-linked immunosorbent assay/immunostaining, we further analyzed various atherosclerosis-related factors. RESULTS: The gross atherosclerotic lesion area in the aortic arch increased by 15.3% in high-fat-diet rabbits exposed to TSST-1 compared to that in the control group. In the atherosclerotic lesions, TSST-1 exposure increased the content of smooth muscle cells. Moreover, TSST-1 treatment up-regulated serum tumor necrosis factor alpha (TNF-α) level, but did not affect serum lipids (except for triglycerides) and endotoxin in the rabbits. CONCLUSIONS: Our data validated that chronic stimulation with TSST-1 facilitates the progression of atherosclerosis in rabbits independently of endotoxins, indicating that S. aureus and its SAgs may be targets to prevent and treat atherosclerosis.